In the absence of the gift new forms of value and personhood in a Papua New Guinea community - Rasmussen, Anders Emil (Pacific perspectives : studies of the European society for oceanists, 2015)
"By adopting ideas like 'development,' members of a Papua New Guinean community find themselves continuously negotiating what can be expected of a relative or a community member. Nearly half the people born on the remote Mbuke Islands become teachers, businessmen, or bureaucrats in urban centers, while those who stay at home ask migrant relatives 'What about me?' This detailed ethnography sheds light on remittance motivations and documents how terms like 'community' can be useful in places otherwise permeated by kinship. As the state withdraws, Mbuke people explore what social ends might be reached through involvement with the cash economy"--Provided by publisher